2019
DOI: 10.1002/jhet.3635
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Sulfonamide‐Based 5‐Arylidenerhodanines as Effective Carbonic Anhydrase (II) Inhibitors: Microwave‐Assisted and Ultrasound‐Assisted One‐Pot Four‐Component Synthesis, Molecular Docking, and Anti‐CA II Screening Studies

Abstract: The synthesis of N‐substituted‐5‐arylidenerhodanines was carried out by the optimized one‐pot sequential four‐component procedure with the condensation between 4‐aminobenzenesulfonamide, suitable aldehyde, ethyl bromoacetate, and carbon disulfide. In addition to traditional method, microwave‐irradiated and ultrasound‐irradiated techniques were implemented in water at ambitious conditions, and the target compounds were obtained in high yields and purity without purification methods. The enzyme inhibition activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Then, triethylamine and corresponding aromatic aldehyde (4) was added to the reaction mixture and sonicated for 5 min in order to carry out the final step of intramolecular ring closure. Considering the optimization studies examining the effect of the base on the reaction and our groups' previous studies,22,23 it was achieved high reaction yields by using TEA in the range of 81%–94%. The structures of purified compounds were verified by FTIR, MALDI‐TOF/MS, 1 H‐NMR, and 13 C‐NMR spectroscopy (Supplementary File).…”
Section: Resultsmentioning
confidence: 93%
“…Then, triethylamine and corresponding aromatic aldehyde (4) was added to the reaction mixture and sonicated for 5 min in order to carry out the final step of intramolecular ring closure. Considering the optimization studies examining the effect of the base on the reaction and our groups' previous studies,22,23 it was achieved high reaction yields by using TEA in the range of 81%–94%. The structures of purified compounds were verified by FTIR, MALDI‐TOF/MS, 1 H‐NMR, and 13 C‐NMR spectroscopy (Supplementary File).…”
Section: Resultsmentioning
confidence: 93%
“…Synthesized compounds were also subjected to molecular docking studies and were docked into active site of hCA II. It was observed that compounds 1190g (Ar = 4-NO 2 ) and 1190j were found to have excellent binding energies of value −11.23 and −9.300 kcal/ mol and 1190j also formed bond hydrogen bond with Asn62 and Thr199 [197] (Scheme 181). benzaldehyde 1192 in presence of ethanol and KOH to afford chalcone derivative 1193(a-f) followed by treatment with hydrazine hydrate to obtain desired compounds 1194(a-f).…”
Section: Abdelmentioning
confidence: 99%
“…Synthesized compounds were also subjected to molecular docking studies and were docked into active site of hCA II. It was observed that compounds 1190g (Ar = 4‐NO 2 ) and 1190j were found to have excellent binding energies of value −11.23 and −9.300 kcal/mol and 1190j also formed bond hydrogen bond with Asn62 and Thr199 [ 197 ] (Scheme 181).…”
Section: Chemistry Of Heterocycles As Ca Inhibitorsmentioning
confidence: 99%
“…To determine the K m , V max , K i values and inhibition type of the inhibitor compound with the smallest IC 50 between the studied inhibitor compounds; the Lineweaver-Burk curve was created by using two distinctive inhibitor concentrations (20 µM and 40 µM) at a substrate concentration ranging from 0.01-1.25 mM [16,18,19].…”
Section: Inhibition Type K M V Max and K I Valuesmentioning
confidence: 99%